Analyse de l’activité professionnelle d’un conseiller pédagogique d’Education Physique et Sportive : de la difficulté à superviser le travail d’un enseignant débutant - Stéphane Brau-Antony; Vincent Grosstephan (Recherches en Éducation)
The purpose of this article is to describe and understand the dynamics of the interactions between an educational adviser and his/her trainee teacher during an advice interview which follows a Sport and Physical Education (PE) session. Three sorts of data have been collected: an audio-video recording of the PE session, an audio-video recording of the post-session interview between the educational adviser and the trainee teacher, and an autoconfrontation interview from which the educational adviser had to make comments on the filmed data of his/her activity. The results allowed to highlight on the one hand the content of the speech as well as the different attitudes adopted by the educational advisor during the advice interview, and on the other hand a set of professional difficulties that he/she encountered to manage his/her interview.